MODERN RESOURCE-SAVING TECHNOLOGIES IN FOUNDRY PRODUCTION OF JSC «MINSK TRAKTOR PLANT» - F. A. Domotenko; S. I. Sirotenko; A. N. Karas; A. P. Melnikov; S. I. Sirotenko; G. I. Pasyuk (Литьë и металлургия)
In article the main world tendencies of development of the production technology of sandy cores and value of this production in complex technology of manufacture of castings are considered. It is established that the most rational way of production technically and economically is manufacture of wafer sandy cores using the Cold-box-amin technology. Scientific, technical, technological and economic aspects of modernization of foundry production of JSC MTZ with complete transition to production of sandy cores on the resource-saving Cold-box-amin technology are provided. The main distinctive feature of this reequipment – all planned works are based on the domestic technological developments and the equipment created in the cooperation by specialists of JSC BELNIILIT and JSC MTZ. Within GNTP essential support to the provided works was given by the state.